2012
DOI: 10.1210/jc.2011-2797
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in Children Born to Hypothyroid Mothers Restored to Normal Thyroxine (T4) Concentration by Late Pregnancy in Japan: No Apparent Influence of Maternal T4Deficiency

Abstract: In iodine-sufficient areas, maternal T₄ deficiency in early pregnancy does not necessarily affect neurodevelopment. Therefore, other potential factors altering neurodevelopment, such as iodine deficiency, must be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…According to a hospital-based study in Japan, SCH might be induced by an iodine excess during early pregnancy, but there was no association between serum TSH above 4.9 μU/ml during early pregnancy and child developmental testing (Orito et al 2009). It is also reported that children born to women with hypothyroidism at early pregnancy and whose condition was restored to a normal thyroxine concentration by late pregnancy had a normal neurodevelopmental outcome (Momotani et al 2012). We showed that elevated TSH detected until mid pregnancy was not associated with an overall adverse pregnancy event when considering low prevalence of thyroid autoimmunity.…”
Section: Discussionmentioning
confidence: 49%
“…According to a hospital-based study in Japan, SCH might be induced by an iodine excess during early pregnancy, but there was no association between serum TSH above 4.9 μU/ml during early pregnancy and child developmental testing (Orito et al 2009). It is also reported that children born to women with hypothyroidism at early pregnancy and whose condition was restored to a normal thyroxine concentration by late pregnancy had a normal neurodevelopmental outcome (Momotani et al 2012). We showed that elevated TSH detected until mid pregnancy was not associated with an overall adverse pregnancy event when considering low prevalence of thyroid autoimmunity.…”
Section: Discussionmentioning
confidence: 49%
“…However, in a recent report (11), women who had severe hypothyroidism in early pregnancy, but who were restored to normal later in pregnancy, had offspring who developed normally. The authors postulate that iodine deficiency may be the factor that leads to abnormal development.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, a paper reported that maternal T4 deficiency in early pregnancy does not necessarily affect neurodevelopment 19) .…”
Section: Discussionmentioning
confidence: 97%